Catholic, Irish and Nationalist: evaluating the importance of ethno‐national and ethno‐religious variables in determining nationalist political allegiance in Northern Ireland. Issue 2 (4th March 2013) - Evans, Jocelyn; Tonge, Jonathan
Abstract Irish national identity, political nationalism and Catholicism are the defining characteristics of the minority community in Northern Ireland. These identifiable ethno‐national and ethno‐religious characteristics have been the basis of communal solidarity that has transcended increasing socio‐economic heterogeneity within that community. Both of the Nationalist political parties in Northern Ireland, Sinn Féin and the Social Democratic and Labour Party (SDLP), draw their support almost exclusively from their community of origin. What is not known, however, is the relative importance of Irishness, Catholicism and Nationalism in shaping support for either party. Which of these ethnic identifiers is of greatest salience in identifying support for Sinn Féin or the SDLP? Drawing upon recent election survey evidence, this article attempts to rectify this information deficit, highlighting the weighting of components of ethnicity in determining intra‐bloc political allegiances.